2010
DOI: 10.1088/0952-4746/30/1/002
|View full text |Cite
|
Sign up to set email alerts
|

Key factors in imprecision in radiological emergency response assessments using the NAME model

Abstract: In the very early stages of response to an accidental release of radioactivity leading to environmental contamination, it is likely that only limited measurements of radioactivity in the local environment will be available on which to base decisions concerning protection measures and radiation monitoring activities. Model predictions will be used to aid understanding of the radiological situation and to form a basis for emergency health protection decisions. This paper presents an analysis of the relative impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The inputs into an emergency assessment tool will often not be well defined in the early stages of an emergency. The key categories of these sources of imprecision, as identified in Haywood et al (2010) can be summarised as:…”
Section: Inclusion Of Imprecisionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inputs into an emergency assessment tool will often not be well defined in the early stages of an emergency. The key categories of these sources of imprecision, as identified in Haywood et al (2010) can be summarised as:…”
Section: Inclusion Of Imprecisionmentioning
confidence: 99%
“…Previous articles (Haywood 2008, Haywood et al 2010 have identified the key contributors to the imprecision in model predictions of local dispersion and doses following an accidental release of radioactivity to atmosphere, considering the early stages of an accident. Both the R91 Gaussian model (Clarke 1979) and the UK Met Office's NAME (Numerical Atmospheric dispersion Modelling Environment version 5.2) dispersion model (Jones et al 2007) were used, and the key parameters were found to be essentially the same, namely uncertainty in the weather (in particular the rainfall rate and the wind direction and fluctuations), the release duration and the dry deposition velocity for those radionuclides for which deposition contributes significantly to dose.…”
Section: Introductionmentioning
confidence: 99%
“…However, these are only some of the uncertainties faced by emergency managers and recovery teams in responding to a nuclear accident. The modelling and analysis of dose, while reducing some of the uncertainties, introduces further ones related to the model choices and the computation (Haywood, 2010;Haywood et al, 2010). Then there are ambiguities and value uncertainties that arise when the managers try to contextualise emergency plans with their imperatives to minimise the risk to "human health" or some such objective to the specifics of the accident and those affected (French et al, 2016).…”
Section: Introductionmentioning
confidence: 99%